Filipina in the web a semiotic analysis of top ten websites for the keyword filipina - Dy, Glory Pearl A.
Filipina in the web: a Semiotic Analysis of Top Ten Websites for the Keyword?Filipina? is a thesis that looks into the general representation of the Filipina in the Web. This study aimed to find out if the Filipina in web search engines ? particularly on the first page (or top 10 sites) of the three Wen search engines: Google, MSN, and Yahoo- is generally viewed as a sex and dating objects. It also sought to understand, by looking at the daily trends of the website, the viewing dynamics of users interested on the Filipina. It also attempted to identify who contributed to the optimization of the website with the use of the keyword ?Filipina?. Finally, the study tried to find out if the images displayed on the phone pages of the top 10 websites contributed to the representation of the Filipina online. Using Geroge Drilon's Writing the Images (2003) and Juan C. Dursteler's ?Visual Rhetoric? (2008), images from the top ten websites were analyzed. Each image was generated from the top ten websites from a comparison of top ten optimized websites from three different search engines: Google, MSN, and Yahoo. The results showed that the massages presented by the images were straightforward. The representation of the Filipina in the web was greatly affected by ethical issues, with a number of graphic images addressed to specific audiences. The number of images affected the optimization of a particular representation. The three search engines ? Google, Yahoo, and MSN ? dominantly employed a negative representation of the Filipina as strongly contributed by the number of images found in optimized websites from Google. Based on the results of the study, consistency of the number and the theme of the images as well as links with the number of keywords for a particular site affected the ranking of sites. The scattered placement of images, excluding the footer, revealed that the entire space of the homepage was important to attract audiences. Emotional arguments were shown to be important in persuasive representation. Most of the contributing viewers of negative sites dominantly come from the Philippines. The significance of this thesis is that it can identify the representation of Filipina in the Web, thus easily targeting specific negative representations. It can identify the type of meaning of the images and their respective rhetorical skills to persuade audience interests. It can help call for a more websites to employ a positive representation of the Filipina. It can provide suggestions how to eliminate sites that employ a negative representation of the Filipina or sites that present Filipina as dating and/or sex objects. Finally, it can provide suggestions for further studies to organizations involved in feminist and gender issues.